Predictability of persistent frequent attendance in primary care: a temporal and geographical validation study. - Frans T Smits (Public Library of Science (PLoS), 2013)
Background Frequent attenders are patients who visit their general practitioner exceptionally frequently. Frequent attendance is usually transitory, but some frequent attenders become persistent. Clinically, prediction of persistent frequent attendance is useful to target treatment at underlying diseases or problems. Scientifically it is useful for the selection of high-risk populations for trials. We previously developed a model to predict which frequent attenders become persistent. Aim To validate an existing prediction model for persistent frequent attendance that uses information solely from General Practitioners' electronic medical records. Methods We applied the existing model (N = 3,045, 2003-2005) to a later time frame (2009-2011) in the original derivation network (N = 4,032, temporal validation) and to patients of another network (SMILE; 2007-2009, N = 5,462, temporal and geographical validation). Model improvement was studied by adding three new predictors (presence of medically unexplained problems, prescriptions of psychoactive drugs and antibiotics). Finally, we derived a model on the three data sets combined (N = 12,539). We expressed discrimination using histograms of the predicted values and the concordance-statistic (c-statistic) and calibration using the calibration slope (1 = ideal) and Hosmer-Lemeshow tests. Results The existing model (c-statistic 0.67) discriminated moderately with predicted values between 7.5 and 50 percent and c-statistics of 0.62 and 0.63, for validation in the original network and SMILE network, respectively. Calibration (0.99 originally) was better in SMILE than in the original network (slopes 0.84 and 0.65, respectively). Adding information on the three new predictors did not importantly improve the model (c-statistics 0.64 and 0.63, respectively). Performance of the model based on the combined data was similar (c-statistic 0.65). Conclusion This external validation study showed that persistent frequent attenders can be prospectively identified moderately well using data solely from patients' electronic medical records.